Dampak Alokasi Dana Desa, Jumlah Wajib Pajak, Jumlah Penduduk dan Luas Lahan terhadap Realisasi Penerimaan PBB-P2 - Halimatus Sa’diyah; Diyah Probowulan; Achmad Syahfrudin Z (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to partially determine the effect of the impact of Village Fund Allocation, Population and Land area on the Realization of PBB-P2 Revenue in Jember Regency. This research is a quantitative study using survey research methods. The population of this study was all villages in Jember Regency, the sample was 44 villages with PBB-P2 acceptance that met the target. Sampling using a purposive sampling technique. Data was collected through secondary data from literature studies and documentation of local tax revenue realization. Data analysis uses multiple linear regression. The results of the Village Fund Allocation research variable, obtained a significant value of 0.006 <0.05, which means that the Village Fund Allocation partially has a significant impact on the realization of PBB-P2 revenue. The variable number of taxpayers has a significant value of 0,000 <0.05 which means it has a significant impact on the realization of PBB-P2 revenue. Variable Number of population with a value of 0,000 <0.05 means that it has a significant impact on the realization of PBB-P2 revenue. Variable land area with sig. 0,000 <0.05, can be interpreted as having a significant impact on PBB-P2 Revenue. Conclusion The more land area utilized by the population, plus the number of residents and the number of taxpayers has a significant impact on increasing the realization of PBB-P2 revenue, while the amount of Village Fund Allocation has a partially significant impact on the realization of PBB-P2 revenue Keywords: Village Fund Allocation, Number of Taxpayers, Population, Land Area, Acceptance of Rural and Urban Land and Building Taxes